Kesadaran dan Kesiapsiagaan Bencana pada Masyarakat Pesisir Kalimantan Utara - Ahmat Pujianto; Maria Imaculata Ose; Putri Intan Baydhuri; Mellisa Chelsea Azzahra Santoso Putri (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2025)
The role of disaster awareness and preparedness in improving disaster preparedness in the community is vital. The relationship between disaster awareness and disaster preparedness in coastal communities has not been directly ascertained, so research is needed to assess the problem. The purpose of this study was to identify the relationship between disaster awareness and disaster preparedness in coastal communities. This study is a correlational and cross-sectional study. This study involved 100 respondents using an convenience sampling technique. This research was conducted in one of the coastal sub-districts of Tarakan City, North Kalimantan Province. The data collection process was carried out from October to November 2024. The disaster awareness and preparedness assessment instrument used a questionnaire from previous research. The Chi-Square test was used to see the relationship between disaster awareness and disaster preparedness. The results showed that most respondents were female (58%), worked as farmers/fishermen (33%), graduated from high school/vocational school (41%), the average age of respondents was 37.33 years with an average income of Rp1,626,000 per month. Most respondents with low disaster awareness also had low disaster preparedness (53%). The results of the Chi-Square test showed that there was a relationship between disaster awareness and disaster preparedness (p = 0.001). The low disaster awareness and disaster preparedness in coastal communities, it is necessary to provide disaster education to the community so that the community is ready to face disaster conditions, especially in coastal areas.